Mediation of Psychological Capital in the Relationship of Altruistic Leadership and Employee Innovative Behavior - Melaty Riza (Yayasan Education Al Aqsho Modern, 2023)
This research was conducted at the ASN of the Department of Industry, Trade, Cooperatives, Small and Medium Enterprises of Riau Province with the aim of examining the influence of altruistic leadership on innovative behavior of employees with psychological capital as mediation. The sample determination method used in this study was systematic sampling, based on the Krejcie and Morgan (1979) table, with N = 216 (rounded to 220), so the total sample was 140 people. Analysis of the research data used descriptive statistics and verification analysis, as an analytical tool used the Structural Equational Model which was processed with SmartPLS2 Software. The results of the analysis prove that altruistic leadership has a significant positive effect on employee innovative work behavior, psychological capital has a significant positive effect on employee innovative work behavior, and psychological capital is able to mediate the effect of altruistic leadership on employee innovative work behavior.